2021
DOI: 10.1039/d1ob00111f
|View full text |Cite
|
Sign up to set email alerts
|

Recent advances in the synthesis and applications of β-keto sulfones: new prospects for the synthesis of β-keto thiosulfones

Abstract: The review mainly focuses on the recent developments in preparing β-keto sulfones and their enormous synthetic applications. New prospects for the synthesis of β-keto thiosulfones have also been highlighted. Over...

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
12
0

Year Published

2021
2021
2023
2023

Publication Types

Select...
10

Relationship

2
8

Authors

Journals

citations
Cited by 54 publications
(12 citation statements)
references
References 129 publications
0
12
0
Order By: Relevance
“…β-Ketosulfones are key structural skeletons in many bioactive molecules, and their synthetic methods developed so far are predominantly through homogeneous catalysis. , For example, the photoinduced oxysulfonylation of readily available alkynes with sulfonylhydrazides could be achieved with 2 mol % Ru­(bpy) 3 Cl 2 as the photocatalyst . Mechanistic studies suggested that the vinyl radical is the key intermediate which traps molecular oxygen during the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…β-Ketosulfones are key structural skeletons in many bioactive molecules, and their synthetic methods developed so far are predominantly through homogeneous catalysis. , For example, the photoinduced oxysulfonylation of readily available alkynes with sulfonylhydrazides could be achieved with 2 mol % Ru­(bpy) 3 Cl 2 as the photocatalyst . Mechanistic studies suggested that the vinyl radical is the key intermediate which traps molecular oxygen during the reaction.…”
Section: Resultsmentioning
confidence: 99%
“…Among sulfone-type compounds, β-keto-sulfones are a class of valuable chemical intermediates. 60 In 2020, the Xu group reported the oxysulfonylation of alkenes toward β-ketosulfones ( 35 ) using sulfonyl hydrazides ( 33 ) and styrenes ( 34 ) with an electrochemical method ( Scheme 6 ). 61 To obtain the desired products, an undivided cell equipped with an RVC anode and a Pt cathode was employed.…”
Section: Sulfonylation Of Alkenes and Alkynesmentioning
confidence: 99%
“…The general approach to the synthesis of β-ketosulfones is the nucleophilic substitution reaction of sodium sulfonates with α-haloketone [20][21][22]. One representative method for the preparation of β-ketosulfones involves Cu-catalyzed direct C-S cross-coupling of various oxime acetates with sodium sulfinates to construct a C(sp 3 )-S bond reaction [23][24][25][26][27][28][29][30][31][32][33][34][35][36]. Alternatively, various β-ketosulfones can be prepared through the Cu-catalyzed direct C-S coupling reaction of substituted alkenes with various sulfonylhydrazides under an oxygen atmosphere.…”
Section: Introductionmentioning
confidence: 99%